Analisis Model Pembelajaran NHT Dalam Meningkatakan Kemampuan Berpikir Kritis - Diratna Briliandika; Deni Adi Putra; Kunti Dian Ayu Afiani (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to analyze the NHT learning model for improving students' critical thinking skills. Numbered Head Together (NHT) is a numbered head learning model whose members and groups are heterogeneous; then, the teacher randomly calls the number from the student so that each student has his obligation and checks the student's understanding of the learning material. This research was qualitative research with literary study research. The research was carried out by collecting data using books and various journals related to the required research variables. The search results obtained nine articles from journals and one from the repository. Based on the analysis results, it turns out that the Numbered Heads Together (NHT) learning model can improve students' thinking skills, starting from an average of 51.6% with the lowest percentage value being 6% and the highest reaching 133%. In addition to improving students' critical thinking, the Numbered Head together model might also make students more active in discussing each other to solve problems and understand the material. Keywords: Numbered Heads Together (NHT), Critical Thinking Skill